Effects of Aerosol Scattering Attenuation on Free-Space Optical Link Performance in Owerri, Southeast, Nigeria - S. A. Akinwumi; O. A. Ayo-Akanbi; T.V. Omotosho; T. A Arijaje; O. O. Ometan; O. M. Adewusi (Science and Technology: Developments and Applications Vol. 8, 2025)
High-speed, point-to-point data transmission through laser beams across terrestrial networks is sometimes referred to as "Free-Space Optics" (FSO). Multimedia applications including social networks, OTT platforms, video conferencing, and multimedia streaming are driving up the demand for data rates and channel bandwidth, which has led to a telecommunications bottleneck. In spite of the several benefits of using free-space optical (FSO) communication systems as complementary platforms for next-generation networks, the existence of atmospheric disturbances such as fog and scintillations are key sources of signal impairment that affect system performance. Thus, it is crucial to learn about the specific weather patterns of the areas where FSO lines will be installed. The purpose of this work is to estimate the availability performance of FSO lines broadcasting at both 850 nm and 1550 nm by performing a statistical analysis of meteorological visibility data gathered for Owerri in Nigeria over a 21-year period (2000-2021). The results show that the visibility during the most common fog events in Owerri is 100 meters. The probabilities of encountering and exceeding the scattering attenuations associated with Owerri’s most common fog event are 0.0002 and 0.0229, respectively. This research could be expanded in the future by exploring the effects of varying localized climatic conditions on the many forms of optical signals, such as plane, spherical, and Gaussian beam waves. This would aid in the modelling of different forms of attenuation for deployment sites of FSO or hybrid FSO systems.